Adventure tourism: a study of Tunku Abdul Rahman Park, Sabah - Nik Alif Amri Nik Hashim; Sun, Boyd Fatt; Tini Maizura Mohtar; Zaimatul Awang; Raja Norliana Raja Omar; Eni Noreni Mohamad Zain; Munirah Mahshar; Muhammad Jaffri Mohd Nasir (Ubiquity Press, 2020)
Adventure tourism is one of the main travel activities in the world. For instance, adventure tourism is among the primary contributors to the economy in Sabah, which is undertaken by most travellers who visit the state. This study was conducted to identify the perceptions of the local Sabahan visitors regarding adventure tourism activities at Tunku Abdul Rahman Park. Other than identifying the services and activities offered at Tunku Abdul Rahman Park, this study also seeks to examine how adventure tourism activities impact the environment of the islands. A 300 set of self-administrated questionnaires were distributed to the local visitors of Tunku Abdul Rahman Park islands (Manukan, Mamutik, Sapi, and Gaya). It was found that the majority of the local visitors indeed know about adventure tourism activities and they were satisfied with the services and activities offered at Tunku Abdul Rahman Park. While adventure tourism activities are deemed unharmful to the environment as they are believed to benefit the economy, it remains imperative that the infrastructure on the islands be improved. This study will benefit policymakers and tourism operators in Malaysia, especially in Sabah with insightful findings for the Sabah Parks management and Sabah Tourism Board in undertaking promotional ideas that pique the interests of potential tourists to visit the islands whilst sustaining the long-term environment of the islands.